2001
DOI: 10.1246/cl.2001.364
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Process on the Mechanisms and the Performances of the Preferential Crystallization: Example with (±)-5-(4-Bromophenyl)-5-methylhydantoin

Abstract: Resolution of the title compound is carried out at a two liter scale via two different processes of preferential crystallization (PC), the Auto Seeded Programmed Polythermic Preferential Crystallization (AS3PC) process and the classical Seeded Isothermal Preferential Crystallization (SIPC) process. The ratio, crystal growth rate/secondary nucleation rate, is strongly under the influence of the process. Consequently AS3PC process appears more efficient than SIPC process in terms of purity of the crops (optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…This trend corresponds to observations made for conglomerate forming systems. 15,23 During the cyclic isothermal preferential crystallization, the productivities decrease explicitly with increasing cycle number due to the accumulation of decomposition products as discussed before. To avoid decomposition of mandelic acid in the cyclic auto-seeded polythermal crystallization experiments, the crystallizer was covered with opaque material, and the highest process temperature was reduced to <308C.…”
Section: Feasibility Of Preferential Crystallization In the Cyclic Opmentioning
confidence: 83%
See 1 more Smart Citation
“…This trend corresponds to observations made for conglomerate forming systems. 15,23 During the cyclic isothermal preferential crystallization, the productivities decrease explicitly with increasing cycle number due to the accumulation of decomposition products as discussed before. To avoid decomposition of mandelic acid in the cyclic auto-seeded polythermal crystallization experiments, the crystallizer was covered with opaque material, and the highest process temperature was reduced to <308C.…”
Section: Feasibility Of Preferential Crystallization In the Cyclic Opmentioning
confidence: 83%
“…13 For the polythermal preferential crystallization an additional option exists based on generating seeds (a) via in situ nucleation and growth of both species and subsequent selective dissolution of one species 12 or (b) via addition of finely ground or sieved quasi-eutectic feed material and subsequent selective dissolution of one species. 6,10,12,14,15 In Figures 1 and 2 are shown the temperature profiles as well as the process trajectories in the ternary phase diagram for application of the seeded isothermal and the auto-seeded polythermal process for enantioseparation of racemic compound forming systems. For the polythermal process, the seed formation according to principle (b) is demonstrated here.…”
Section: Performance Of Preferential Crystallization As Seeded Isothementioning
confidence: 99%
“…Auto-seeded process [67][68][69]. When compared to the seeded and isothermal process, the auto-seeded and polythermic preferential crystallization appears somewhat as a preferential growth because crystals are bigger (and easier Chapter 22 • Crystallization of Chiral Molecules 977 to filtrate) [70], yields are improved, the process is usually more reproducible and robust, and it can easily be scaled up [71]. Thus, the starting point of the process corresponds to a suspension of a pure enantiomer and there is no need for seeding.…”
Section: Resolution By Preferential Crystallizationmentioning
confidence: 99%
“…Usually SIPC gives poorer results than AS3PC. 34 Preferential crystallization via a metastable conglomerate 22,36,37 On rare occasions, it can be shown that the presence of a stable racemic compound is not the condemnation of the preferential crystallization. Most of these cases correspond to situations depicted in Fig.…”
Section: Benefits Of Conglomeratesmentioning
confidence: 99%